Is That a Real Theory or Did You Just Make It Up? - Odis E. Simmons (Grounded Theory Review: An International Journal)
The title of this paper was derived from an incident I observed some years ago while accompanying a highly talented musician-songwriter friend to a performance. During a break, an audience member approached him to compliment the last song he had performed. He had written both the music and the lyrics to the song, one of many he had written. The audience member queried, “Is that a real song, or did you just make it up?” A touch amused, and not knowing whether he should be flattered or insulted, he politely replied, “It is a real song and I made it up.”